2015
DOI: 10.1055/s-0035-1548733
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Thoracoscopic Surgery versus Video-Assisted Thoracoscopic Surgery for Lung Lobectomy: Can a Robotic Approach Improve Short-Term Outcomes and Operative Safety?

Abstract: Background Minimally invasive surgery has been recently recommended for treatment of early-stage non-small cell lung cancer. Despite the recent increase of robotic surgery, the place and potential advantages of the robot in thoracic surgery has not been well defined until now. Methods We reviewed our prospective database for retrospective comparison of our first 28 video-assisted thoracoscopic surgery lobectomies (V group) and our first 28 robotic lobectomies (R group). Results No significant difference was sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Our results confirm this finding, and show that the benefit of robotic approach is greatest for high-risk patients. High-risk patients are likely underrepresented in many current robotic lobectomy series, as surgeons may tend to select more straightforward cases when adopting new techniques [ 13 ]. One common concern has been the risk of postoperative air leak with a robotic approach, due to the lack of tactile feedback when manipulation diseased lungs, as well as the need for more dissection in the fissure, which could lead to increased risk of air leak.…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm this finding, and show that the benefit of robotic approach is greatest for high-risk patients. High-risk patients are likely underrepresented in many current robotic lobectomy series, as surgeons may tend to select more straightforward cases when adopting new techniques [ 13 ]. One common concern has been the risk of postoperative air leak with a robotic approach, due to the lack of tactile feedback when manipulation diseased lungs, as well as the need for more dissection in the fissure, which could lead to increased risk of air leak.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller 2015 comparison ( 29 ) of the first 28 VATS lobectomies with the first 28 robotic lobectomies performed in a single institution reported that perioperative outcomes were similar for both techniques during the learning period but that the robotic approach was associated with better safety and fewer conversions for uncontrolled bleeding.…”
Section: Robotic Surgery Versus Vats For Major Lung Resections: a Promentioning
confidence: 99%
“…In the last decade, RATS have been amply proven in its feasibility and safety ( 3 , 4 ). Although VATS has been found as being better than open thoracotomy in terms of its lesser invasiveness ( 5 , 6 ), and RATS is associated with a shorter hospital stay and fewer postoperative complications than thoracotomy ( 7 ), RATS requires fewer emergency conversions to open thoracotomy and is associated with lower mortality compared with VATS ( 1 , 8 ).…”
Section: Introductionmentioning
confidence: 99%